Rhodium‐Catalyzed Synthesis of Chiral Monohydrosilanes by Intramolecular C−H Functionalization of Dihydrosilanes - Ma, Wenpeng; Liu, Li‐Chuan; An, Kun; He, Tao; He, Wei (Angewandte Chemie International Edition, 2021)
The preparation of chiral monohydrosilanes remains a rarely achieved goal. To this end a Rh‐catalyzed desymmetrization of dihydrosilanes by way of intramolecular C(sp2)−H functionalization under simple and mild conditions has now been developed. This method provides easy access to a broad range of chiral monohydrosilanes in good yields with excellent enantioselectivities (up to >99 % ee). The resulting monohydrosilanes constitute a good platform to access stereogenic silicon compounds, as well as useful compounds to probe silicon stereochemistry. A Rh‐chiral diphosphine complex was found to catalyze desymmetrization of dihydrosilanes by formal intramolecular Si−H/C−H dehydrogenative coupling reactions. This simple, mild, and practical method results in unprecedently high enantioselectivity and a broad substrate scope. The chiral monohydrosilanes could be further elaborated into various stereogenic silicon compounds in a stereospecific manner.